What about the surphase? - Bristow, J Anthony (Journal of Print and Media Technology Research, 2023)
We talk glibly of the surface of paper, even when we are talking e.g. of paper strength, where we should more correctly talk of the surphase strength. The strength is related to a material layer not to a geometrical surface.